Implantation and Annealing of Aluminum in 4H Silicon Carbide - Rambach, Martin; Schmid, Frank; Krieger, Michael; Frey, Lothar; Bauer, Anton; Pensl, Gerhard; Ryssel, Heiner (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2005)
Aluminum ions with a dose between 1.2 × 1014 cm -2 and 1.2 × 1015 cm-2 were implanted into 4H silicon carbide at room temperature, 650 °C, and 800 °C. High temperature furnace and lamp annealing of the implanted samples were investigated with respect to sheet resistance, hole mobility and free hole concentration. For an aluminum dose of 1.2 × 1015 cm -2 implanted at room temperature and subsequent furnace annealing at 1700 °C for 30 min, a sheet resistance of about 34 kΩ/□ and for lamp annealing at 1770 °C for 5 min, a slight increased sheet resistance of 38 kΩ/□ was obtained. Increasing implantation temperature to 800 °C and postimplantation furnace annealing resulted in a decreased sheet resistance of 18 kΩ/□. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2017-07-10:Pub.2005.nat.dphy.IAP.LAP.implan
Keywords: Annealing; Hall scattering factor; Implantation temperature; Mobility; Sheet resistance; Silicon carbide